Theatrical space and time: a proposal for a semiotic approach - Gutiérrez Flórez, Fabián (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
Starting out from the triple division of Semiotics proposed by Ch. Morris and resorting to the conceptual dichotomies, text / representation and diegesis / mimesis, the author offers a new theoretical reflexion about time and space in theather. The model developed is applied to the analysis of works by A. Gala y A. Buero Vallejo. From a methodological point of view it is considered the presence in theater of textual, espectacular and extra-theatrical time and space: A) textual: diegetic (story) / mimetic (discourse), B) spectacular: scenic (representation) / theatrical (space / time of the public), and C) extra-theatrical (real or possible time and space). It is also considered the basic mode of analysis: syntactical: consideration of diegetic/ mimetic space and time and the relationship between both textual categories; semantical, description of the possible meaning of diegetic / mime tic space and time and its relationship to extra-theatrical space and time; pragmatical: analysis of the relationship between textual and spectacular space and time. With such a theory in hand, it is considered then in detail the triple selective reduction operated by author, director and public over space and time in the theater. First, the author transforms extra-theatrical space and time into diegetic space and time, and then dramatizes this result into mimetic formo Second, the director organizes spectacular (scenic) space and time starting out form textual space and time and taking into account theatrical space and time. And final!y, the public at the end of the reception process integrates al! spaces and times at work into a coherent whole.